2012
DOI: 10.1590/s0100-40422012001000024
|View full text |Cite
|
Sign up to set email alerts
|

Formaldeído em escolas: uma revisão

Abstract: Recebido em 5/3/12; aceito em 6/6/12; publicado na web em 31/8/12 FORMALDEHYDE IN SCHOOLS: A REVIEW. Formaldehyde has been classified as a probable human carcinogen. Indoor air quality measurements carried out worldwide in schools indicate that levels may be of concern. This paper provides an overview of emission sources, properties and methods for quantification of formaldehyde. Quantitative information from studies performed in school environments was compiled and a comprehensive picture of the causal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…These environments combined with an increase in humidity and temperature (physical parameters) can lead to the appearance of a large number of fungi and bacteria (biological parameters) (Fraga et al, 2008). These parameters have become a study base regarding the IAQ since these can be found, for example in cleaning products, materials and/or damaged equipment and polluted, due to human presence, their activities and poor conditions of ventilation and air renewal (Schirmer et al, 2011); (Alves, 2012). Due to the multiple pollutants that can be found in a building, the WHO has classified "Sick Building Syndrome" (SBS) as a danger to public health.…”
Section: -Theoretical Frameworkmentioning
confidence: 99%
“…These environments combined with an increase in humidity and temperature (physical parameters) can lead to the appearance of a large number of fungi and bacteria (biological parameters) (Fraga et al, 2008). These parameters have become a study base regarding the IAQ since these can be found, for example in cleaning products, materials and/or damaged equipment and polluted, due to human presence, their activities and poor conditions of ventilation and air renewal (Schirmer et al, 2011); (Alves, 2012). Due to the multiple pollutants that can be found in a building, the WHO has classified "Sick Building Syndrome" (SBS) as a danger to public health.…”
Section: -Theoretical Frameworkmentioning
confidence: 99%
“…Formaldehyde could originate from composite wood and other products with urea-formaldehyde resin, some architectural finishes, tobacco smoke and other combustion processes. Also, pressed wood products use adhesive containing urea formaldehyde that can break down, releasing formaldehyde into the air (Alves and Aciole, 2012). In spring and summer, outdoor formaldehyde levels increase due to acceleration of photochemical activity (Lee et al, 2001), while the opposite trend is observed indoors, since the interchange rate between indoor and outdoor air is higher due to open windows (Pilidis et al, 2009).…”
Section: Air Pollutantsmentioning
confidence: 99%
“…Formaldehyde it is obtained through the oxidation of methanol and manufactured in a 37% (w/v) aqueous solution (Alves & Aciole, 2012). It is considered a simple aldehyde, having only one carbonyl carbon attached to two hydrogens -HCHO (Russel, 1994;Atkins & Jones, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a simple aldehyde, having only one carbonyl carbon attached to two hydrogens -HCHO (Russel, 1994;Atkins & Jones, 2011). It is a colorless, volatile liquid compound and exhibits a strong and irritating odor, in addition, it is soluble in water, toxic in high concentrations and can be flammable (Alves & Aciole, 2012). Since it is a volatile compound, consumers and professionals who use this product category (hair straighteners) containing formaldehyde are highly affected, both by its irritating effect on the scalp, and more especially by the inhalation of this compound causing harmful effects to the health (Abraham et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%